Sigma Force: The Eye of God - Book 9 - Rollins, James 1961- (New York, NY : William Morrow, An Imprint of HarperCollinsPublishers, 2013)
Commander Gray Pierce and Sigma Force set out to discover a truth tied to the fall of the Roman Empire, to a mystery going back to the birth of Christianity, and to a weapon hidden for centuries that holds the fate of humanity.
Keywords: Special operations (Military science) -- Fiction; Code and cipher stories; Suspense fiction